La vraie France : Psichari, Péguy, Bloy, Claudel, Mauriac, Maritain, Pétain, Copeau, Ghéon, Dom Bellot - Gilmard (1941)
Conjunto de estudios sobre la obra de diez autores católicos franceses del siglo XX del período de entre guerras.